Countless Blessings : A History of Childbirth and Reproduction in the Sahel - Cooper, Barbara M.; Cooper, Barbara M. (Book collections on Project MUSE., 2019)
Introduction -- Environment, seduction, and fertility -- Tensions in the wake of conquest : gender and reproduction after abolition -- Personhood, socialization, and shame -- Colonial accounting -- Perils of pregnancy and childbirth -- Producing healthy babies and healthy laborers -- Feminists, Islamists, and demographers -- Let's talk about bastards -- Contemporary sexuality and childbirth -- Conclusion: Traveling companions and entrustments in contemporary Niger.